Impact of services trade liberalization on employment and people movement in South Asia - Rupa Chanda (Asian Development Bank Institute (ADBI), 2011)
Services have been a key driver of overall economic growth in South Asia since the 1990s. This paper examines how the growth of services output, trade and investment have affected service sector employment in South Asia and the extent to which countries in this region are proactively undertaking skill development, training, and human resource management policies that are targeted at the service sector.
Keywords: F14; F16; F22; F23; 330; services; service sector employment; service sector; south asia; Handelsliberalisierung; Dienstleistungshandel; Investition; Bruttoinlandsprodukt; Erwerbstätigkeit; Dienstleistungssektor; Südasien